Resurrecting FUS: Adrenal Androgens as an Ultimate Cause of Hematuria, Periuria, Pollakuria, Stranguria, Urolithiasis and Obstruction in Neutered Cats - Reines, Brandon P.; Wagner, Robert A. (Frontiers in Veterinary Science, 2018)
Although many authors have doubted that “feline urological syndrome” (FUS) describes a real pathogenetic entity, because it subsumes such a large variety of symptoms, Sumner’s recent finding that urethral obstruction occurs most frequently in Spring adds to a large body of evidence that lower urinary tract problems occur most commonly in late winter and spring. This suggests that FUS may be a unitary disorder, with a hormonal basis, driven by increasing day length. We argue that rising adrenal androgens (AA) in neutered cats induce stress, and other more concrete manifestations of FUS through androgen-driven mechanisms.